Biodiversity of Aflatoxigenic Aspergillus Species in Dairy Feeds in Bulawayo, Zimbabwe - Nleya, Nancy; Ngoma, Lubanza; Adetunji, Modupeade C.; Mwanza, Mulunda (Frontiers in Microbiology, 2021)
The presence of molds, especially certain species of Aspergillus, in food commodities may contribute to aflatoxin contamination. The aim of this study was to determine the biodiversity of Aspergillus species in dairy feeds from farms in select locations in Zimbabwe and assess their aflatoxin production potential using a polyphasic approach. A total of 95 feed samples were collected, which consisted of dairy feed concentrate mixed ration, brewers’ spent grain and grass from 13 farms during the dry season (August- October, 2016) and the following rainy season (January-March, 2017). A total of 199 presumptive isolates representing four sections from genus Aspergillus (Nigri, Fumigati, Flavi and Circumdati) were recovered from the feeds. Section Flavi, which includes several aflatoxin producers, constituted 23% (n=46) of the isolates. Species from this section were A. flavus, A. nomius, A. oryzae, A. parasiticus and A. parvisclerotigenus, and 39 (84.4%) of these showed evidence of aflatoxin production in plate assays. Of the 46 section Flavi isolates examined, some lacked one or more of the five targeted aflatoxin cluster genes (aflD, aflR, aflS, aflM and aflP). The presence of the 5 genes was as follows; aflD (76.9%), aflR (48.7%), aflS (74.4%), aflM (64.1%) and aflP (79.5%). This study highlights the species diversity of aflatoxigenic fungi that have the potential to contaminate different types of feed for dairy cows. Our findings underscore the importance of preventing contamination of feedstuffs by these fungi so that aflatoxins do not end up in the diets of consumers.